Hak Kekayaan Intelektual Bagi Produk Kreatif Usaha Kecil Menengah dengan Perlindungan Hukumnya Di Kabupaten Buleleng - I Gusti Agung Wisnu Satria Wangsa; I Gusti Ngurah Dharma Laksana (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Indonesia is known as a state of law that has regulated various protections of ideas in the form of innovation and creativity that have various economic values ​​through many laws and regulations related to Intellectual Property Rights. This is very necessary because as we know Indonesia has enormous potential in the creative industry and abundant natural resources. The rapid development of the creative industry in Indonesia greatly contributes to the country's economic growth. Where it can be seen from year to year there are always updates and additions to the number of creative products both from young people and community groups engaged in entrepreneurship. The existence of UMKM and their policies have been implemented and used through several laws and regulations, in the context of developing the business climate, including Law No. improve the expertise and position and institutions of Micro, Small, and Medium Enterprises in the national economy. Various aspects and actions of the government covering many things in terms of production, marketing and branding are carried out so that MSMEs are able to compete in the national and international realm. economy through many laws and regulations related to Intellectual Property Rights. This is very necessary because as we know Indonesia has enormous potential in the creative industry and abundant natural resources. The rapid development of the creative industry in Indonesia greatly contributes to the country's economic growth. Where it can be seen from year to year there are always updates and additions to the number of creative products both from young people and community groups engaged in entrepreneurship. The existence of UMKM and their policies have been implemented and used through several laws and regulations, in the context of developing the business climate, including Law No. improve the expertise and position and institutions of Micro, Small, and Medium Enterprises in the national economy. Various aspects and actions of the government covering many things in terms of production, marketing and branding are carried out so that UMKM are able to compete in the national and international realm.